Post Subject : A Fable - De la Paz, Oliver, 1972- (Book collections on Project MUSE., 2014)
"Ecstatic and obsessive, the prose poems that make up Oliver de la Paz's Post Subject: A Fable reveal the monuments of a lost country. Through a series of epistles addressed to "Empire" a catalog emerges, where what can be tallied is noted in a ledger, what can be claimed is demarcated, and what has been reaped is elided. The task of deposing the late century is taken up. What's salvaged from the remains is humanity"--